The legacy of middle school leaders : in their own words - Smith, Tracy W.; McEwin, C. Kenneth (Handbook of resources in middle level education., 2011)
Sponsored by the Middle Level Education Research SIG of AERA, this inaugural volume in the new IAP book series, The Handbook of Resources in Middle Level Education, focuses on the contributions and impact of the leaders of the modern middle school movement. Contained with this volume are the edited transcripts from 20 extensive interviews of the most influential leaders of the middle level movement, including such notable figures as William Alexander, Donald Eichhorn, John Lounsbury, Conrad Toepfer, and Gordon Vars. This historic volume will be an invaluable resource to proponents, advocates, and students of the middle school concept and developmentally appropriate education for young adolescents.